Novel Regulation of Fibroblast Growth Factor 2 (FGF2)-mediated Cell Growth by Polysialic Acid - Ono, Sayaka (American Society for Biochemistry and Molecular Biology, 2012)
Polysialic acid (polySia) is a unique polysaccharide that modifies neural cell adhesion molecule (NCAM) spatiotemporally. Recently, we demonstrated that polySia functions as a reservoir for several neurotrophic factors and neurotransmitters. Here, we showed the direct interaction between polySia and fibroblast growth factor-2 (FGF2) by native-PAGE, gel filtration, and surface plasmon resonance. The minimum chain length of polySia required for the interaction with FGF2 was 17. Compared with heparan sulfate, a well known glycosaminoglycan capable of forming a complex with FGF2, polySia formed a larger complex with distinct properties in facilitating oligomerization of FGF2, as well as in binding to FGF receptors. In polySia-NCAM-expressing NIH-3T3 cells, which were established by transfecting cells with either of the plasmids for the expression of the polysialyltransferases ST8SiaII/STX and ST8SiaIV/PST that can polysialylate NCAM, FGF2-stimulated cell growth, but not cell survival, was inhibited. Taken together, these results suggest that polySia-NCAM might be involved in the regulation of FGF2-FGF receptor signaling through the direct binding of FGF2 in a manner distinct from heparan sulfate.